COMPREHENSIVE GERIATRIC ASSESSMENT IN ELDERLY PATIENTS AT THE EMERGENCY AND STROKE DEPARTMENT, NATIONAL GERIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the results of the Comprehensive Geriatric Assessment (CGA) among older patients admitted to the Emergency and Stroke Department at the National Geriatric Hospital, and to determine the association between CGA components and short-term clinical outcomes.Methods: A cross-sectional study was conducted on 229 patients aged ≥60 years treated between September 2024 and September 2025. Each patient underwent a CGA within 24–48 hours after admission, including assessments of ADL, IADL, Mini-Cog, GDS-15, CAM-ICU, MNA-sf, CFS, fall risk, polypharmacy, and comorbidities. Clinical outcomes were categorized as discharge, referral, or poor outcome (death/discharge against advice).Results: The mean age was 76.5 ± 7.6 years; 42.8% were aged ≥80 years. Males accounted for 55.9%. Impairment rates: ADL 76.8%, IADL 78.6%, cognitive impairment 34.9%, delirium 31,9%, depression 36,2%, malnutrition 21.8%, high fall risk 44.1%, frailty 60.3%, and polypharmacy 52%. Outcomes: 53.3% discharged, 32.8% referred, 14.0% poor outcome. Five independent predictors of poor outcome included advanced age (OR=1.079; p=0.018), lower ADL (OR=0.750; p=0.032), delirium (OR=2.697; p=0.016), higher CFS (OR=1.390; p=0.022), and higher fall risk (OR=1.204; p=0.017).Conclusion: CGA in emergency settings allows early detection of critical geriatric syndromes such as functional decline, delirium, and frailty, supporting early intervention to improve outcomes among older adults.
Keywords: Comprehensive Geriatric Assessment; elderly; emergency; frailty; prognosis; treatment outcomes.